Image compression using Thresholding Techniques (International Journal of Engineering and Computer Science, 2017)
Image compression Using Thresholding Techniques i.e Global Thresholding , By Level Thresholding addresses the problem of reducing the amount of data required to represent a digital image. The rapid development of high performance computing and communication has opened up tremendous opportunities for various computer-based applications with image and video communication capability. However, the amount of data required to store a digital image is continually increasing and overwhelming the storage devices. The data compression becomes the only solution to overcome this. Image compression is the representation of an image in digital form with as few bits as possible while maintaining an acceptable level of image quality . The redundancy can be removed to achieve compression of the image data i.e., the fundamental components of compression are redundancy andirrelevancy reduction. The basic measure of the performance of a compression algorithm is the compression ratio, which is defined by the ratio between original data size and compressed data size.Higher compression ratios will produce lower image quality and vice cersa is also true.